Computationally Assisted Assessment of the Metal‐Organic Framework/Polymer Compatibility in Composites Integrating a Rigid Polymer. Issue 11 (16th August 2019) - Tavares, Sergio Rodrigues; Ramsahye, Naseem Ahmed; Adil, Karim; Eddaoudi, Mohamed; Maurin, Guillaume; Semino, Rocio
Abstract: Density functional theory (DFT) calculations and subsequent classical molecular dynamics (MD) simulations are combined to build and further characterize the interface structure of three binary metal‐organic framework (MOF)/polymer composite materials made of ultra‐small pore MOFs with distinct surface morphologies, namely, MIL‐69, ftw ‐MOF‐ABTC, and ftw ‐MOF‐BPTC, and the 6‐FDA‐DAM polymer. It is found that the three composites exhibit percolated or independent microvoids of different degrees of interconnectivity, sizes, and positions at the MOF/polymer interface that contribute to decrease the polymer surface coverage, a signature of a relatively poor adhesion between the two components. The ftw ‐MOF‐BPTC‐based composite, however, shows a partial penetration of the polymer in the MOF first pore layer, hinting a slightly higher affinity between the MOF and the polymer. These results suggest that even when considering MOFs surfaces with drastically different morphologies, finding a highly compatible MOF/polymer pair for rigid polymers remains challenging. Abstract : The interfacial structure of three metal‐organic framework (MOF)/polymer composites that differ in the identity of the MOF is explored by means of molecular dynamics simulations. Based on their microscopic structure, none of them is expected to exhibit an optimal MOF/polymer compatibility. Compatibility seems to depend more on the rigidity of the polymer than on the MOF surface morphology and decoration.